The presentation pattern and surgical strategies in bronchopulmonary carcinoid tumors: a multicenter experience in a low-income country - Deme, Workneh Tesfaye; Merine, Seyoum Kassa; Wadaja, Desalegn Fekadu; Gemeda, Abdela Hayato; Demissie, Meklit Tamrat; Bahta, Mahlet Tesfaye; Reta Demissie, Wondu (Frontiers in Surgery, 2024)
Background: Bronchopulmonary carcinoid tumors include typical and atypical carcinoids, where typical carcinoids represent 80% to 90%. The primary curative treatment for these tumors is surgical resection. To our knowledge, there are limited studies on presentation patterns and treatment strategies of bronchopulmonary carcinoid tumors in Africa.Objective: To determine presentation patterns and surgical strategies in bronchopulmonary carcinoid tumors in patients treated at multi-centers in Ethiopia from January 2018 to December 2023.A 5-years retrospective cross-sectional study was conducted using medical record and pathology record review of patients operated on inTikur Anbessa Specialized Hospital, Menelik II Hospital, and Saint Peter's Specialized Hospital from January 1, 2018, to December 31, 2023. The completeness of data was checked before being entered into Epidata version 4.6.1 and analysis was done using SPSS version 29. Logistic regression was applied to depict the association of the histological pattern with its predictors. A P value of < 0.05 was considered significant for the association of variables.Results: A total of 62 patients with bronchopulmonary carcinoid tumors were included in the study with a mean age of 35.29 + 12.26 years ranging from 14 -67 years, where more than half of them [37(56.5%)] were females with male to female ratio of 1:1.3. Majority of the patients were non-smokers (90.3%) and symptomatic (98.4%) with the mean duration of symptoms of 29.7 + 26 months ranging from 3 -156 months. Nearly half of the patients (48.4%) were treated for pulmonary tuberculosis before a diagnosis of carcinoid tumor was made. The majority of the patients underwent surgery by open posterolateral thoracotomy approach (98.4%) and pneumonectomy was the most common (38.7%) resection performed. The typical carcinoid was observed in 85.5% of patients. Age, smoking history, duration of symptoms, location of tumors, and lymph node status were statistically associated with histologic patterns.Recommendation: Based on our study findings; awareness creation for physicians on the clinical presentation of carcinoid tumors, training on less invasive surgical approaches for surgeons, and nationwide further study is recommended.